THE MORPHOLOGY OF PERMANENT UPPER FIRST MOLARS EVALUATED BY CONE-BEAM COMPUTED TOMOGRAPHY IN A BRAZILIAN SUBPOPULATION (CIPEEX, 2023)
This study was conducted with the aim of evaluating the variations in the morphology of permanent maxillary first molars, assessed by cone-beam computed tomography in a Brazilian subpopulation. For each tooth, data regarding gender, number of roots and root canals, and root anatomy were analyzed, based on the Vertucci classification (1984). The sample of this cross-sectional study was composed of 111 cone-beam computed tomography scans of patients referred for diagnostic purposes, of both sexes, aged between 18 and 80 years. After applying the exclusion criteria, the final sample consisted of 167 tomographic examinations of upper first molars. After analyzing the images, it was found that all the teeth had three roots, and of these, 85.62% had three canals (n=143) and 14.37% had four canals (n=24). Regarding Vertucci's classification (1984), type I was the most prevalent canal configuration (84%) in the mesio-buccal canals, 5% were classified as type II (n=9), 7% as type III (n=11), 2% as type V (n=3), and 2% as type VI (n=4). There was a low prevalence (1%) of type III classification in the disto-buccal canals, with the remaining (99%) classified as type I. It is concluded that from the cone beam computed tomography images, it was possible to assess the number of roots and the morphology of root canals, elucidating their most frequent variations.
Keywords: Vertucci Classification; cone beam computed tomography; molars; anatomy